MANAJEMEN STRATEGI PENINGKATAN MUTU EKSTRAKURIKULER TAHFIDZ AL-QUR’AN DI SMA ISLAM AL-AZHAR 22 CIKARANG KABUPATEN BEKASI - Ulfa Ispiani Pratiwi (Jurnal Kinerja, 2023)
This study aims to determine management strategies in improving the quality of extracurricular tahfidz Al-Qur'an at SMA Islam Al-Azhar 22 Cikarang. The focus of this research is how to plan strategic management to improve the quality of tahfidz extracurriculars at Al-Azhar 22 Islamic High School Cikarang, implement management strategies to improve the quality of tahfidz extracurriculars at Al-Azhar 22 Islamic High School Cikarang, and evaluate management strategies for improving the quality of tahfidz extracurriculars at Islamic High Schools. Al-Azhar 22 Cikarang. This study used a qualitative method which took the research location at SMA Islam Al-Azhar 22 Cikarang. Data collection methods are observation, interviews, documentation. The results of this study indicate that to improve the quality of tahfidz extracurricular activities at Al-Azhar 22 Islamic High School Cikarang there are several programs that have been implemented, namely, the 6SQ program, Tahfidz supercamp activities, in collaboration with the tahfidz institution Raudhatul Jannah, holding MABIT activities (Night of Faith and Taqwa) . This effort was made so that Al-Azhar Islamic High School can achieve the goals set in its vision and mission, namely to make Al-Azhar 22 Cikarang Islamic High School students the Qur'anic generation